How do you answer a 20-year-old when they ask: can I participate in competitive sports? Long questionnaire - Sachdeva, A. (Cardiology Practice, 2021)
The sudden, unexpected death of a young athlete is a tragedy unparalleled in sports, which leads to grief among friends, family members and community. Sudden death in athletes attracts large amounts of media attention. Expanding the current criteria for pre-participation screening in young athletes may improve outcomes in some cases. The recommendations and opinions have varied from obtaining a detailed history and physical examination alone to use of an electrocardiogram (ECG). The addition of an echocardiogram, computed tomography (CT) scan, cardiac magnetic resonance imaging (CMR), stress test and Holter monitor for rhythm monitoring when indicated can substantially improve the diagnostic ability of the treating clinician.